A Study of the Symbiotic Relationship Between Traditional and New Media in China and Its Impact on the Marketing Strategies of Chinese Enterprises - Wang Y., Xu W. (Strategies of Sustainable Development: Social, Law and External-economic Aspects, 2024)
this study examines the evolution of the communication landscape in China, highlighting the symbiotic fusion of traditional and new media and its profound implications for the marketing strategies of Chinese enterprises. Statistical analysis emphasises the steady dominance of traditional media, with television, newspapers and radio retaining significant audience shares. In contrast, the growing landscape of new media, exemplified by platforms such as WeChat, Weibo and Douyin, demonstrates unprecedented digital penetration. The empirical prevalence of both media modalities calls for a realignment of marketing strategies: market segmentation, cross-media campaigns, neuroscience research and algorithmic modelling become key tools to optimise brand resonance and consumer engagement.
Keywords: маркетинговые стратегии; new media; традиционные медиа; новые медиа; симбиотические отношения; взаимодействие медиа; traditional media; symbiotic relationship; marketing strategies; media interaction